The economics of the business firm : seven critical commentaries - Demsetz, Harold, 1930-2019 (Cambridge University Press, 1995)
The essays in this volume discuss the theory of the business firm and its applications in economics. A leading analyst of industrial organization, Professor Demsetz first critically examines current debates on the existence, definition, and organization of the firm and discusses conceptual and theoretical issues related to the emerging theory of the firm. He then analyzes contemporary treatments of the relation between business ownership, wealth, and economic development. Subsequent essays offer new perspectives on competition, profit maximization and rational behavior, and shed new light on managers' compensation, antitrust policy, and the accuracy of firms' accounting data. The latter themes will interest business audiences as well as professionals and students in economics. These previously unpublished essays derive from lectures originally presented at Uppsala and Lund Universities in Sweden, the Mont Pelerin Society meeting in Prague, and the Center for the Study of Economics and the State at the University of Chicago.